DualCFGL: dual-channel fusion global and local features for sequential recommendation - Shuxu Chen; Yuanyuan Liu; Chao Che; Ziqi Wei; Zhaoqian Zhong (Complex & Intelligent Systems)
Abstract Sequential recommendation systems capture the dynamic interests of users and predict their future preferences. A noteworthy problem in sequential recommendation is coping with the intrinsic changes of user interests. The sequence of user interactions is generated by more than a single and stable global preference, users may have interest drift that occur in a short period of time. We call this short-term interest drift as the local preference of users, which is often a key factor affecting the final choice of users. However, existing methods have limitations in observing local preferences, which leads to an incomplete consideration of the local preferences. Moreover, using a single model to represent global–local preferences obscure the distinct features of each, limiting the potential synergistic benefits. To alleviate the above limitations, we propose a novel model with a dual-channel structure to monitor both global and local preferences and ensure they complement each other. The model extracts the global preferences of users with a bidirectional Transformer using random masking and a sliding window, and extracts the local preferences with a patch-based stacked bottleneck residual convolution. To enable the model to consider both the global and local preferences of users, we design an adaptive orthogonal fusion module, which effectively fuses the two preferences and enables the two feature types to complement and enhance each other. We integrate the fused user preferences with a knowledge distillation method that further improves the model’s expressive ability. We conduct extensive experiments on three widely used datasets, and the results show that our model outperforms current state-of-the-art models.